Analisis Komunikasi Media Sosial dalam Bidang Militer : Twitter/X TNI Al (@_Tnial_) Sejak 2018-2022 - Inas Alya Haura (Lembaga Kajian Pertahanan Strategis, 2025)
Today we live in an interconnected digital world. Social media is present as a pervasive component in this digital era whose presence dominates our lives. Facebook, Twitter or X, and Instagram all provide modern forms of engagement for organizations including the Indonesian Navy to the general public. Social media can be utilized by both individuals and groups as an effective form of modern communication and functions as a useful and dynamic interaction tool. Regardless of its good and bad impacts, social media can capture a lot of information regarding organizational operations, responsibilities, projects and related details about Communication Technology. In this paper, we will discuss the results and how the Indonesian Navy military has utilized the use of social media so that it can be represented via Twitter/X social media within a period of five years.